Effect of alternating day and night temperature on short day-induced bud set and subsequent bud burst in long days in Norway spruce - Olsen, Jorunn E.; Lee, YeonKyeong; Junttila, Olavi (Frontiers in Plant Science, 2014)
Young seedlings of the conifer Norway spruce exhibit short day (SD)-induced cessation of apical growth and bud set. Although different, constant temperatures under SD are known to modulate timing of bud set and depth of dormancy with development of deeper dormancy under higher compared to lower temperature, systematic studies of effects of alternating day (DT) and night temperatures (NT) are limited. To shed light on this, seedlings of different provenances of Norway spruce were exposed to a wide range of DT-NT combinations during bud development, followed by transfer to forcing conditions of long days (LD) and 18°C, directly or after different periods of chilling. Although no specific effect of alternating DT/NT was found, the results demonstrate that the effects of DT under SD on bud set and subsequent bud break are significantly modified by NT in a complex way. The effects on bud break persisted after chilling. Since time to bud set correlated with the daily mean temperature under SD at DTs of 18 and 21°C, but not a DT of 15°C, time to bud set apparently also depend on the specific DT, implying that the effect of NT depends on the actual DT. Although higher temperature under SD generally results in later bud break after transfer to forcing conditions, the fastest bud flush was observed at intermediate NTs. This might be due to a bud break-hastening chilling effect of intermediate compared to higher temperatures, and delayed bud development to a stage where bud burst can occur, under lower temperatures. Also, time to bud burst in un-chilled seedlings decreased with increasing SD-duration, suggesting that bud development must reach a certain stage before the processes leading to bud burst are initiated. The present results also indicate that low temperature during bud development had a larger effect on the most southern compared to the most northern provenance studied. Decreasing time to bud burst was observed with increasing northern latitude of origin in un-chill